(untitled) (Advances in Military Technology, 2022)
It followed from the results of firing tests conducted with particulate grenade models under variable weather conditions in the field that the models generated a particulate aerodispersion in a cloud effective for a short time. The tested kinds of particles produced clouds of aerodispersions of similar sizes; the cloud diameters were increasing upwardly up to the 20th second after the explosive action of spreading the charge up to the value of diameter l = 13 m in the case of Chezarb, l = 20 m in the case of the S244 carbon fibres, l = 22 m in the case of brass particles, and l = 28 m in the case of aluminium particles. Particulate systems in the cloud showed good attenuating capabilities for a short time in the whole IR range of spectrum. The tests proved that their application in the multispectral protection of military objects is desirable.